Nature: A Substantial Source of Auspicious Substances with Acetylcholinesterase Inhibitory Action - Orhan, Ilkay Erdogan (Bentham Science Publ Ltd, 2013)
Acetylcholinesterase (AChE) (EC 3.1.1.7) is an important enzyme that breaks down of acetylcholine in synaptic cleft in neuronal junctions. Inhibition of AChE is associated with treatment of several diseases such as Alzheimer's disease (AD), myasthenia gravis, and glaucoma as well as the mechanisms of insecticide and anthelmintic drugs. Several AChE inhibitors are available in clinical use currently for the treatment of AD; however, none of them has ability, yet, to seize progress of the disease. Consequently, an extensive research has been going on finding new AChE inhibitors. In this sense, natural inhibitors have gained great attention due to their encouraging effects toward AChE. In this review, promising candidate molecules with marked AChE inhibition from both plant and animal sources will be underlined.
Keywords: Acetylcholinesterase; cholinesterase inhibition; neuroprotection; herbal; animal; microorganism